Comprehensive Geriatric Assessment in primary healthcare: a scoping review protocol - Luiz Santiago; Inês Rosendo; António Luís Vidinha Pereira; Ana Vaz; Constança Paúl (BMJ Open)
Objectives To compile and compare the Comprehensive Geriatric Assessment (CGA) models that exist worldwide and their applicability in primary healthcare (PHC).Introduction The world’s population is ageing rapidly, but health systems are slow to keep up with this trend, making it difficult to provide care for older adults. The broad concept of frailty has prompted a comprehensive and holistic approach to patients, where the assessment is related not only to functional, physical and cognitive abilities of the older adults, but also their social, environmental and economic context. In recent decades, the approach to frailty has taken the CGA as the gold standard. With this project, we intend to carry out a scoping review to identify and describe tools to help standardise and generalise CGA in PHC.Inclusion criteria Individuals aged 65 years or over; CGA in a PHC setting; the CGA methods reported must include at least three domains: physical, cognitive and social; Articles without language restrictions; Articles published in the last 30 years.Methods All studies that refer to CGA models and fulfil the inclusion criteria will be selected. A bibliographic search of articles will be carried out using the following electronic scientific publication databases: MEDLINE-PubMed, Embase, Cochrane Library and Web of Science. We will search for grey literature on sites such as ‘OpenGrey’ and thesis repositories such as RCAAP, EBSCO and EThOS, as well as on the WHO pages. The articles will be independently selected by two reviewers, and the data will be presented in narrative format, structured according to the objective, focus and question of the review.Ethics and dissemination Approved by the ethics committee of the regional health administration of the centre, registered as Project 11/2024 and approved on 8 May 2024. The findings of this study will be disseminated through peer-reviewed publications and national or international conference presentations. Updates of the review will be conducted, as necessary.Trial registration number Open Science (DOI 10.17605/OSF.IO/REH43).